Respuesta :

Explanation:

Distributive property: → [tex]a(b+c)=ab+ac[/tex]

Expand equation.

[tex]6(x-4)[/tex]

Then, multiply 6*4.

[tex]6*4=24[/tex]

[tex]=3x+6x-24[/tex]

Add by similar elements.

[tex]6+3=9[/tex]

Don't forget to used variable with letter/symbol.

[tex]\boxed{9x-24}[/tex]

Hope this helps!

Thank you!

Have a great day!

-Charlie

Hey there!

Answer = 9x - 24

Let's simplify step-by-step.

3x + 6(x - 4)

Distribute:

= 3x + (6)(x) + (6)(-4)

= 3x + 6x + -24

Combine Like terms:

= 3x + 6x + -24

= (3x + 6x + (-24)

= 9x + -24

= 9x - 24

So therefore, that is how you found your answer: 9x - 24